Spatial and temporal distributions in the Norwegian cod fishery. (25th June 2020) - Alizadeh Ashrafi, Tannaz; Eide, Arne; Hermansen, Øystein
Abstract: Fisheries are characterized by variations in space and time. This study investigates the characteristics of seasonality in cod trawl fisheries in two distinct areas: the coast along the northern Norway and the high sea area of the Barents Sea. Catch per unit effort (CPUE) is used to proxy variation in stock abundance. A CPUE function has been estimated in the frequency‐domain framework, to detect the presence of seasonality. Our analysis reveals that seasonality in stock abundance is only present in the northern coast of Norway. We conclude that as a consequence of seasonality in stock aggregation during the first quarter of the fishing year, possible economic losses caused by reduced prices—stemming from a large supply of cod—are larger than the economic benefits from cost reduction per unit of harvest. We speculate that declined price and consequently potential economic losses encourage trawlers to substitute cod by other high‐value fisheries during the winter months. As the price of cod starts to rise after the first quarter, trawlers begin to target cod in the high sea areas, a region with less seasonality. Recommendations for Resource Managers: Taking into account findings, policy formations and management considerations may include: Improving understanding of the spatial and temporal distribution of CPUE. This allows for better long‐ and medium‐term planning of vessel capacity and technology. Allowing also for better planning of the distribution of fishing effort across the year, which improves economic yield. Sharing the result of the study will improve short‐term utilization and economic yield among the fishing fleet. Information on variations in CPUE over time and space may be relevant for authorities and researchers in evaluation of stock abundance.